Peningkatan Prestasi Belajar Ekonomi Melalui Metode Pembelajaran Student Teams Achievement Devision Tahun Pelajaran 2019/2020 - Riyanto Riyanto (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The purpose of this research is to identify whether there is an increase in economic learning achievement in class VIII SMP N 2 Kartasura in the use of the STAD (student teams achievement division) procedure. This type of research is experimental research that intends to equate something as a result of certain treatments. The population in this research is all grade VIII students of SMP Negeri 2 Kartasura for the academic year 2019/2020 which consists of 6 classes with a total of 240 students. On the other hand, the illustration in this research is 1 class (40 students) taken using the Simple Random Sampling method. The required information is obtained through the provision of explanatory tests. The test questions to be used were tested for validity and reliability. Besides that, documentation procedures are used to clarify information. The method of analysis uses normality test, homogeneity test, and makes hypothesis testing with mean difference test (t test). From the results of the analysis it can be concluded that: STAD cooperative education can improve student achievement in class VIII SMP Negeri 2 Kartasura in the 2009/2010 academic year. before the experiment (66, 675) or there is a difference of 14, 4. It means that STAD cooperative education is better (more efficient) in improving student achievement. Keywords: STAD (Student Teams Achievement Division), economics learning achievement